A novel approach to Caputo–Hadamard pantograph problems in L p $\mathfrak{L}^{\mathsf{p}}$ -spaces - Gunaseelan Mani; Purushothaman Ganesh; Kokila Kannan; Maryam Ali Alghafli; Nabil Mlaiki (Boundary Value Problems)
Abstract In this paper, we investigate the existence and uniqueness of solutions for Caputo–Hadamard pantograph fractional differential equations with boundary conditions in L p $\mathfrak{L}^{\mathsf{p}}$ -spaces, by applying fixed-point theorems in L p $\mathfrak{L}^{\mathsf{p}}$ -spaces to prove existence and uniqueness. Stability is analyzed through the Ulam–Hyers stability and Ulam–Hyers–Rassias stability, offering key insights into the reliability of the system. Practical examples are also provided for illustration.